Coated vs. naked red phosphorus: A comparative study on their fire retardancy and smoke suppression for rigid polyurethane foams. (February 2017) - Cao, Zhi-Jie; Dong, Xue; Fu, Teng; Deng, Shi-Bi; Liao, Wang; Wang, Yu-Zhong
Abstract: Red phosphorus (RP) and the coated RP with melamine formaldehyde resin (MFcP) were foamed with isocyanates to prepare polyurethane foam (PUF). The cell size of PUF/RP became uneven and more spherical, and the cell struts became thicker. The cells of PUF/MFcP were much more uniform in size and more spherical in shape. Addition of flame retardants increased the densities, compressive strength and thermal conductivity of the foams, but decreased the blind hole percents. Thermal gravimetric analysis (TGA) tests exhibited that decomposition of both PUF/RP and PUF/MFcP took place at lower temperatures than that of neat PUF. However, the maximum decomposition temperature (Tmax ) for PUF was increased from 300 °C to ca. 340 °C when RP or MFcP was added. Load of RP or MFcP with 80 pphp or higher increased the limiting oxygen index (LOI) of PUF to higher than 25% and pass UL-94 V-0 grade. In the cone calorimetry tests (CC), It indicated that PUF/MFcP100 released much less heat and smoke than PUF/RP100 and PUF. The smoke release of PUF/MFcP100 was reduced by almost 75% than that of PUF/RP100 . The toxic gas release of PUF/MFcP100 was reduced more than 50% than that of PUF/RP100 . The smoke emission of PUF increased significantly after addition of RP comparing with that addition of MFcP greatly relief the situation. The corresponding mechanism was proposed.